THE BUDDHIST PARADIGM FOR CHANGING THE PERSONNEL’S WORKING BEHAVIOR IN ELECTRICAL ENERGY STATE ENTERPRISE - ตั้งปัทมชาติ อดิศักดิ์ (Journal of MCU Social Science Review, 2018)
The Objectives of The Research were 1) to study the changing the personnel’s working behavior in Electrical Energy State Enterprise, 2) to study the factor affecting the changing of personnel’s working behavior in Electrical Energy State Enterprise, 3) to present the Buddhist paradigm for changing the personnel’s working behavior in Electrical Energy State Enterprise The research findings were as follows: 1) the personnel in Electrical Energy State Enterprise should be changed the personnel’s working behavior by adhering virtue morality and ethics, accepting the idea of cause and effect, attending to the social and environmentconscious, learning and working with the other people as a team, and continuous improvement the system correctly and being honest to the organization. 2) The Factor affecting the changing of personnel’s working behavior in Electrical Energy State Enterprise was Vuddhi-Dhamma 4 which consists of (1) associating with a good man (2) knowing to excellence learning from a good man (3) thinking with the critical reflection and (4) knowing to practice in perfect conformity.